Czynniki konkurencyjności gospodarki chińskiej - wybrane aspekty - Ładysz, Iwona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Today the Chinese economy is one of the fastest developing economies in the world. The article discusses selected aspects of competitiveness of the Chinese economy. The most important is liberalization of economic system - first of all step-by-step opening of the Chinese economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 279-286